2012
DOI: 10.1111/j.1525-142x.2012.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of color: developmental origins of divergent pigmentation in Drosophila americana and D. novamexicana

Abstract: Pigmentation is a model trait for evolutionary and developmental analysis that is particularly amenable to molecular investigation in the genus Drosophila. To better understand how this phenotype evolves, we examined divergent pigmentation and gene expression over developmental time in the dark-bodied Drosophila americana and its light-bodied sister species Drosophila novamexicana. Prior genetic analysis implicated two enzyme-encoding genes, tan and ebony, in pigmentation divergence between these species, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…Fine-scale genetic mapping confirmed that divergence at tan was indeed a contributor to pigmentation divergence and localized the functionally divergent sites within tan to the first intron (Wittkopp et al 2009). Subsequent work has shown small, but significant differences in cis -regulatory activity of the D. americana and D. novamexicana tan alleles that presumably contribute to pigmentation differences (Cooley et al 2012). The contribution of tan to pigmentation divergence between these two species was further confirmed when the D. americana tan allele caused darker pigmentation than the D. novamexicana tan allele when each was put into a common D. melanogaster genetic background using transgenes (Wittkopp et al 2009).…”
Section: Abdominal Pigmentationmentioning
confidence: 99%
“…Fine-scale genetic mapping confirmed that divergence at tan was indeed a contributor to pigmentation divergence and localized the functionally divergent sites within tan to the first intron (Wittkopp et al 2009). Subsequent work has shown small, but significant differences in cis -regulatory activity of the D. americana and D. novamexicana tan alleles that presumably contribute to pigmentation differences (Cooley et al 2012). The contribution of tan to pigmentation divergence between these two species was further confirmed when the D. americana tan allele caused darker pigmentation than the D. novamexicana tan allele when each was put into a common D. melanogaster genetic background using transgenes (Wittkopp et al 2009).…”
Section: Abdominal Pigmentationmentioning
confidence: 99%
“…Furthermore, while our observations are based on a small subset of the genome, the genes used are not enriched for particular functional groups, chromosomal location, or magnitude of cis-regulatory differences (data not shown), suggesting that the set is unbiased and that sex3cis-regulatory variant interactions are common, consistent with Massouras et al (2012). These types of interactions can result, for example, from cis-regulatory variants that affect binding sites for trans-regulatory factors that differ between the two sexes Cooley et al 2012), as was reported for the Drosophila desatF gene (Shirangi et al 2009). Figure 2 Relative cis-regulatory activity differed the most between males and females.…”
mentioning
confidence: 99%
“…7.2(A) (Ferguson et al, 2011) ebony antagonizes black melanin formation leading instead to yellowish tan coloration. 7.2(A)), as directly demonstrated by allele specific measurements in species hybrids (Cooley et al, 2012). The causal events underlying this variation are specific cis-regulatory sequence changes which result in decreased ebony expression, and hence darker pigmentation (Rebeiz et al, 2009).…”
Section: Cis-regulatory Evolution Of Pigmentation Patternsmentioning
confidence: 81%